LAND USE CHANGE OF AGRICULTURAL LAND IN A SPATIAL POLITICAL APPROACH - Putri, Rizca Yunike (Journal of Urban Sociology, 2020)
The effort to meet the community's need for space is to change the function of land which was originally used as agricultural activity to become a space for other community activities and is non-agricultural in nature, which we will later call the conversion of agricultural land. Generally, uncontrolled conversion of agricultural land functions, if not addressed, can lead to serious problems, among others, can threaten the capacity of food supply and environmental sustainability. The trend of increasing demand for land makes conversion of agricultural land difficult to avoid. The loss of agricultural land and the conversion of agricultural land to non-agricultural functions regardless of its form are indicators for the development of modern cities. The modern city which is synonymous with industrialization and the splendor of buildings will gradually remove agricultural areas and change the environmental ecosystem further. If viewed from an ecological point of view, of course this problem causes environmental imbalance which will have a negative impact on food security. But what about the conversion of agricultural land from the viewpoint of spatial politics?Keywords: Agricultural land, land use changes, political spatial